RE-MAKING THE LIBRARY MAKERSPACE : CRITICAL THEORIES, REFLECTIONS, AND PRACTICES - Melo, Maggie; Nichols, Jennifer T. (Library Juice Press, 2020)
"Examines the limitations and challenges emerging from the "maker movement" emphasizing the critical work that is being done to cultivate anti-oppressive, inclusive and equitable making environments. Makerspaces in libraries are especially focused upon"